The Representation of Sasak Society in the Text “Gugur Mayang” - Dharma Satrya HD; Zainul Muttaqin (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
This study examines the representation of Sasak society in the text “Gugur Mayang”. It aims to semiotically explain the significance and communication of the text in Sasak culture by applying Paul Ricoeur’s interpretation method. Analysis shows that the “Gugur Mayang” text represents Sasak society while highlighting the sadness, tragedy, and grief of a life that is full of danger and pain. By interpreting the text within sociocultural, spiritual, and literary context, the researchers have been able to obtain a transcendental (rather than empirical) understanding of Sasak society.